Modified ROTEM for the detection of rivaroxaban and apixaban anticoagulant activity in whole blood: A diagnostic test study. Issue 6 (June 2019) - Pailleret, Claire; Jourdi, Georges; Siguret, Virginie; Gouin-Thibault, Isabelle; Gandrille, Sophie; Stepanian, Alain; Curis, Emmanuel; Golmard, Jean-Louis; Gaussem, Pascale; Le Bonniec, Bernard; Samama, Charles M.
Abstract : BACKGROUND: Rapid detection of the anticoagulant effect of oral factor Xa (FXa) inhibitors may be essential in several emergency clinical situations. Specific assays quantifying the drugs are performed in plasma and require a turnaround time that is too long to be useful in emergency situations. Rotational thromboelastometry (ROTEM) is a whole blood coagulation assay of blood viscoelasticity and could be of interest for FXa inhibitor detection in emergency. However, conventional ROTEM reagents only detect high amounts of inhibitors. OBJECTIVE: The aim of this study was first to assess the effect of whole blood components on the viscoelastic measurement of the effects of FXa inhibitors, and second to evaluate whether a modified ROTEM, triggered with a low amount of tissue factor and a saturating amount of phospholipid vesicles, can reliably detect low levels of FXa inhibitor activity in whole blood. DESIGN: Diagnostic test study. SETTINGS: A university research laboratory. From November 2014 to April 2016. PATIENTS: Sixty-six patients: 30 treated with rivaroxaban, 17 with apixaban and 19 without treatment. INTERVENTION: ROTEM was triggered with 2.5 pmol l −1 of tissue factor and 10 μmol l −1 of phospholipid vesicles. MAIN OUTCOME MEASURES: Modified ROTEM parameters were measured in different experimental conditions: platelet-poor plasma (PPP), platelet-rich plasma, PPP supplemented with fibrinogen and reconstituted whole blood with various haematocrit levels adjusted between 30 and 60%. Modified ROTEM was further validated using whole blood from patients who were either treated or not treated with FXa inhibitors. RESULTS: Modified ROTEM allowed detection of as little as 25 ng ml −1 FXa inhibitors in PPP, with at least a 1.4-fold increase of the clotting time ( P  ⩽ 0.02). Neither changes of fibrinogen concentration nor variations of platelet count or haematocrit precluded FXa inhibitor detection. A lengthened modified ROTEM clotting time of more than 197 s allowed detection of FXa inhibitor concentrations above 30 ng ml −1 in whole blood with 90% sensitivity and 85% specificity. CONCLUSION: Modified ROTEM may be applicable in emergency situations for the detection of FXa inhibitors in whole blood. Abstract : Supplemental Digital Content is available in the text